Synthesis and In Vitro Antitumor Evaluation of Some Carbazole‐Based Thiazole, Thiophene, and 1, 3, 4‐Thiadiazole Derivatives. Issue 39 (16th October 2020) - Bondock, Samir; Nasr, Tamer; Alqahtanti, Salwa
Abstract: In continuation to our efforts to discover new powerful antitumor agents, a series of new carbazole‐based thiazole, thiophene, and 1, 3, 4‐thiadiazole derivatives were conveniently synthesized, spectrally characterized, and mechanistically discussed. The synthetic strategy involves the cyclization reactions of two easily attainable commencing materials, N ‐(9‐ethylcarbazol‐3‐yl)‐2‐cyanoacetamide (1 ) and 2‐((9‐ethylcarbazol‐3‐yl)hydrazono)‐3‐oxo‐ N ‐phenylbutanethioamide (20 ), with α‐chlorocarbonyl reagents, α‐chloronitrile, and hydrazonoyl chlorides in a basic medium. They were also assessed against three human tumor cell lines (HCT‐116, HepG‐2, and MCF‐7) and one non‐tumor human cell line (REP1) for their in vitro antitumor activity. The results demonstrated that seven carbazoles 4, 15 a, 15 b, 15 d, 20, 22 b, and 29 a had high antitumor activity, having IC50 values in the range 5.24–9.70 μM. The most potent carbazoles 15 b, 20 and 22 b inhibited the growth of all tested tumor cell lines and did not display human toxicity. Abstract : A novel series of carbazoles bearing thiazole, thiophene, and 1, 3, 4‐thiadiazole units was simply synthesized and studied for their in vitro antitumor activity against colon (HCT‐116), hepatocellular (Hep‐G2) and breast (MCF‐7) carcinoma cell lines beside one non‐tumor cell line (REP1). Among tested carbazoles, compounds 4, 15 d, 22 b, and 29 a reveal the potent anticancer potency with no toxcicity on standard human cell line.